2012
DOI: 10.1186/alzrt153
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of symptomatic treatments for Alzheimer's disease: computational analysis of pathology and mechanisms of drug action

Abstract: IntroductionA substantial number of therapeutic drugs for Alzheimer's disease (AD) have failed in late-stage trials, highlighting the translational disconnect with pathology-based animal models.MethodsTo bridge the gap between preclinical animal models and clinical outcomes, we implemented a conductance-based computational model of cortical circuitry to simulate working memory as a measure for cognitive function. The model was initially calibrated using preclinical data on receptor pharmacology of catecholamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 95 publications
(123 reference statements)
1
65
0
Order By: Relevance
“…Localization of membrane receptors and ion channels and their intracellular regulation is derived from literature and reflects the domain expertise collected in the neuroscience community. Key biological coupling parameters between receptor activation and subsequent change in voltage-gated ion channels are calibrated using a correlation between model outcome and actual historical clinical outcomes for a large number of pharmacological interventions, such as ADAS-Cog changes over time with different doses of acetylcholinesterases and 5-H6 antagonist SB742457 [26].…”
Section: Prediction Of Clinical Outcomes With Quantitative Systems Phmentioning
confidence: 99%
“…Localization of membrane receptors and ion channels and their intracellular regulation is derived from literature and reflects the domain expertise collected in the neuroscience community. Key biological coupling parameters between receptor activation and subsequent change in voltage-gated ion channels are calibrated using a correlation between model outcome and actual historical clinical outcomes for a large number of pharmacological interventions, such as ADAS-Cog changes over time with different doses of acetylcholinesterases and 5-H6 antagonist SB742457 [26].…”
Section: Prediction Of Clinical Outcomes With Quantitative Systems Phmentioning
confidence: 99%
“…Details of the platform have been described elsewhere (Spiros et al, 2010; Roberts et al, 2012b). With regard to cognitive disorders, we have used this platform to explain the differential clinical effect of memantine and apolipoprotein E (APOE) on ADAS-Cog in Alzheimer patients (Roberts et al, 2012b).…”
Section: Quantitative Systems Pharmacologymentioning
confidence: 99%
“…With regard to cognitive disorders, we have used this platform to explain the differential clinical effect of memantine and apolipoprotein E (APOE) on ADAS-Cog in Alzheimer patients (Roberts et al, 2012b). The platform also predicted correctly a completely unexpected phase I outcome in humans with the lowest dose of a novel symptomatic compound on scopolamine-induced deficit that was different from what preclinical animal models suggested (Nicholas et al, 2012).…”
Section: Quantitative Systems Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of blockade of the NMDA receptors is changed according to the concentration of memantine [128]. Memantine is a neuroprotective agent that has completed phase III clinical trial in patients with glaucoma [129,130]. The trial showed that memantine was ineffective by the primary end point, with the variable mechanisms of retinal ganglion apoptosis being offered as an explanation [131].…”
Section: B Neuroprotection By Nmda Receptor Antagonistsmentioning
confidence: 99%